Continuous Ambulatory Peritoneal Dialysis (CAPD) sebagai Terapi Pengganti Ginjal - Safitri, Rini; Sutanto, Agus (CV. Jasa Sukses Abadi, 2025)
Chronic Kidney Disease (CKD) is a major global health concern with a steadily rising prevalence, often progressing to End-Stage Renal Disease (ESRD) that requires Renal Replacement Therapy (RRT). Common modalities of RRT include hemodialysis (HD), peritoneal dialysis (PD), and kidney transplantation. Continuous Ambulatory Peritoneal Dialysis (CAPD) has gained increasing attention as a PD modality offering greater flexibility, cost efficiency, and improved patient quality of life. This review aims to provide a comprehensive overview of CAPD mechanisms, indications, contraindications, management, and potential complications, while also comparing it with hemodialysis in terms of clinical outcomes, cost, and accessibility. Numerous studies have demonstrated that CAPD contributes to better physical, emotional, and psychological well-being, as well as being more cost-effective, particularly in developing countries such as Indonesia. Nevertheless, its implementation remains limited due to challenges in patient education, healthcare provider readiness, and infrastructural support. By enhancing patient training, establishing stronger clinical networks, and integrating CAPD into national kidney care policies, this modality could play a pivotal role in improving the equity and sustainability of renal replacement therapy in Indonesia.